Pelatihan Pembuatan Pupuk Kompos Limbah Peternakan dan Perkebunan bagi Masyarakat Dusun Selelos Kabupaten Lombok Utara - Dharmawibawa, Iwan Doddy; Karmana, I Wayan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this activity is to increase the knowledge and skills of the community in utilizing livestock and community plantation waste into compost. The advantages of this compost are that it is environmentally friendly, can increase the income of farmers and can increase soil fertility and improve soil physical damage due to excessive use of inorganic fertilizers. The participants of this training activity were 21 people from Selelos Baturinggit Village, Gangga District, North Lombok Regency. This training activity is carried out in three stages, namely: 1) Preparation; 2) Implementation; and 3) Evaluation. The implementation of this community service program is by providing a technology package for making solid organic fertilizer with the basic ingredients of cow dung and community plantation waste. Extension activities and practices for making solid organic fertilizers have been carried out in the Selelos Baturinggit Village Community, North Lombok Regency. The results of this organic fertilizer are expected to be applied to plantation land to reduce the use of inorganic fertilizers and increase plantation yields.